2009
DOI: 10.1002/polb.21686
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of gold nanoparticles with polyhedral oligomeric silsesquioxane and incorporation within polymer matrices

Abstract: A new approach to achieve polymer-mediated gold ferromagnetic nanocomposites in a polyhedral oligomeric silsesquioxane (POSS)-containing random copolymer matrix has been developed. Stable and narrow distributed gold nanoparticles modified by 3-mercaptopropylisobutyl POSS to form Au-POSS nanoparticles are prepared by two-phase liquid-liquid method. These Au-POSS nanoparticles form partial particle aggregation by blending with poly(n-butyl methacrylate) (PnBMA) homopolymer because of poor miscibility between Au-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Recently, many literatures reported that the bulky organic and inorganic hybrid POSS nanoparticles could effectively reduce the aggregations of photoluminescence units in the active layers of organic molecule and polymer light-emitting diode devices (OLED [11][12][13][14][15][16] and PLED [17][18][19][20][21][22]). Furthermore, POSS molecules can be regarded as core-shell colloids with solvated alkyl or aryl shells to disperse insoluble siloxane cores in solution [23][24][25][26][27][28][29][30]. In our previous study [31], we found the specific arrangement of alkyl POSS molecules in a crystal.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, many literatures reported that the bulky organic and inorganic hybrid POSS nanoparticles could effectively reduce the aggregations of photoluminescence units in the active layers of organic molecule and polymer light-emitting diode devices (OLED [11][12][13][14][15][16] and PLED [17][18][19][20][21][22]). Furthermore, POSS molecules can be regarded as core-shell colloids with solvated alkyl or aryl shells to disperse insoluble siloxane cores in solution [23][24][25][26][27][28][29][30]. In our previous study [31], we found the specific arrangement of alkyl POSS molecules in a crystal.…”
Section: Introductionmentioning
confidence: 96%
“…The inorganic layered silicate structure of clay, however, does not permit its high dispersion in the organic polymer matrix; therefore, it is essential to pre‐treat the clay with appropriate surfactants 20–22. Recently, novel classes of organic/inorganic hybrid materials based on polyhedral oligomeric silsesquioxanes (POSS) have been developed 23–34. POSS possess an inorganic Si 8 O 12 core, which can be selectively functionalized with seven inert organic hydrocarbon groups and one reactive functional group, or with eight reactive functional groups that may undergo polymerization or cross‐linking 35–44.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum absorption in toluene is at 532 nm for Au NPs. In the framework of the Mie theory, [18][19][20][21] the position of the maximum of the absorption band is determined by the refractive index of the medium surrounding the NPs, while the width is controlled by the particle size. Figure 4 …”
Section: Synthesis Of Dmap Au Npsmentioning
confidence: 99%